Anti-inflammatory and anti-atherosclerotic potential of opuntiol, opuntioside-I, and opuntiol’s silver nanoparticles: The role of cytokines and chemokines - Perbhat Ali; Talat Roome; Tehseen Fatima; Muhammad Usman; Uzma Zaman; Talat Mirza; Zamara Sarwar; Zara Aslam; Shaheen Faizi; Muhammad Raza Shah (Future Journal of Pharmaceutical Sciences)
Abstract Background Disruption of immune system leads to excessive inflammation and the development of serious autoimmune diseases including atherosclerosis, characterized by the accumulation of oxidized low-density lipoproteins (ox-LDL) and various immune cells, particularly macrophages in the arterial wall. Monocyte chemoattractant protein-1 (MCP-1), stimulated and recognized by ox-LDL and toll-like receptors (TLRs), respectively, triggers intracellular signaling cascades, leading to the excessively released of various cytokines and chemokines. The expression control at any level is of great importance in decreasing the overall cascade of immune responses and inflammation, specifically, atherosclerosis. One of the most promising areas of research in the pathogenesis of inflammation and atherogenesis is herbal medications and its bioactive compounds with better delivery to target the exact cell and tissues with high efficacy and fewer side effects in pharmaceutical exploration. Therefore, the aim of present study was to explore the anti-inflammatory effects of naturally derived compounds, i.e., opuntiol (OP), opuntioside-I (OPG), and opuntiol’s silver nanoparticles (OP-Ag) for achieving optimal therapeutic approach to address the underlying inflammatory processes in atherosclerosis and improving treatment outcomes. Zymosan-induced peritonitis mouse model and ox-LDL was employed to determine the inhibitory potential of these compounds on the expression levels of key cytokines and chemokines allied with the onset of inflammatory events during atherosclerosis. Results qRT-PCR and ELISA were employed to check the expression levels of various cytokines (IL-1β, TNF-α, IL-6), chemokines (MCP-1, KC), and a transcription factor (NF-ĸB). Significant reduction was observed in chemotaxis along with decreased expression of key intermediates in response to the natural extracts, i.e., OP, OPG. Its silver-based nanoparticles and OP-Ag in lower concentration enhanced the drug delivery with improved inhibitory roles. Conclusion Overall, the present findings hold promise for advancing the potential therapeutic effects of OP, OPG, and its OP-Ag nano-conjugates at minimum concentrations, especially in the inflammation characteristic of atherosclerosis context, by incorporating zymogen-induced ox-LDL model where it interacts with TLRs in triggering inflammatory responses, and subsequently simulate atherosclerotic conditions via upregulation of MCP-1.